The effect of early autism intervention on parental sense of efficacy in a randomized trial depends on the initial level of parent stress. (October 2021) - Estes, Annette; Yoder, Paul; McEachin, John; Hellemann, Gerhard; Munson, Jeffrey; Greenson, Jessica; Rocha, Marie; Gardner, Elizabeth; Rogers, Sally J
This study examined whether style or intensity of child-focused intervention had a secondary effect on parental sense of efficacy and whether these effects varied by baseline level of parent stress. We randomized 87 children with autism, age 13–30 months, into one of four conditions: 15 versus 25 intervention hours crossed with 12 months of Early Intensive Behavioral Intervention versus Early Start Denver Model. Baseline parent stress was the putative moderator. Parent sense of efficacy, collected at baseline and the end of treatment, was the dependent variable. Analyses used generalized linear mixed model with full information maximum likelihood estimation. We tested main effects and interactions involving time, treatment intensity and style, and baseline parent stress to test moderation effects. Changes in parent efficacy across 12 months were related to intervention intensity but not style; this effect was moderated by level of parent stress at baseline. Parents with higher stress at the beginning of a 1-year, home-based, comprehensive intervention program had a higher sense of parenting efficacy if their child received lower intensity intervention; parents with lower stress at baseline had a higher sense of efficacy if their child received higher intensity intervention. Lay abstract: This is a study of the secondary effects of interventions for young children with autism on their parents. Specifically, we were interested in the impact on parent's sense of efficacy, or how confident and competent a parent feels about themselves as a parent. We tested three ideas: (1) that the style of the intervention, whether it was more or less structured and whether the parent had a more or less formal role, would impact a parent's sense of efficacy; (2) that the intensity of the intervention, how many hours per week the intervention was delivered, would impact parental efficacy; and (3) that the parent's level of stress prior to intervention would impact how intensity and style effected efficacy. We randomly assigned 87 children with autism, age 13–30 months, into one of four conditions: 15 versus 25 intervention hours crossed with two different styles of intervention. We used statistical tests to examine these ideas. We found that parental efficacy was related to intervention intensity but not style. Parents with higher stress at the beginning of a 1-year, home-based, comprehensive intervention program had a higher sense of parenting efficacy if their child received lower intensity intervention; parents with lower stress at baseline had a higher sense of efficacy if their child received higher intensity intervention. If a parent can emerge from the process of diagnosis and early intervention with an increased sense that they can make a difference in their child's life (i.e. increased sense of efficacy), it may set the stage for meeting the long-term demands of parenting a child with autism.